2018
DOI: 10.20897/ejsteme/3875
|View full text |Cite
|
Sign up to set email alerts
|

Fostering Inquiry and Creativity in Early Years STEM Education: Policy Recommendations from the <i>Creative Little Scientists</i> Project

Abstract: Creative Little Scientists was a 30-month (2011-2014) EU/FP7-funded research project focusing on the synergies between early years science and mathematics education and the development of children's creativity, in response to increasing interest in these areas in European educational policy. Using a variety of methods, including desk research, a teacher survey and classroom-based fieldwork, the research provided insights into whether and how children's creativity is fostered and appropriate learning outcomes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 22 publications
3
16
0
4
Order By: Relevance
“…STEM education is believed to be an important approach to prepare students with essential skills for a competitive workforce in the 21st century [1][2][3] and to meet the increasing need in STEM areas [4,5]. However, successfully implementing STEM education in primary and secondary schools entails different challenges.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…STEM education is believed to be an important approach to prepare students with essential skills for a competitive workforce in the 21st century [1][2][3] and to meet the increasing need in STEM areas [4,5]. However, successfully implementing STEM education in primary and secondary schools entails different challenges.…”
Section: Discussionmentioning
confidence: 99%
“…The integrated approach of STEM (science, technology, engineering, and mathematics) education can foster students' essential skills such as creativity, problem solving, and collaboration to develop a competitive workforce in the 21st century [1][2][3]. Moreover, STEM education may shape students' aspirations for STEM careers and encourage them to pursue STEM careers to meet the increasing need for trained professionals in STEM areas [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies had evaluated the effectiveness of STEM approaches on creativity development. In Western countries, several researchers have developed STEM integration module for all levels of education including preschool (Bicer et al, 2019;Conradty & Bogner, 2019;Conradty et al, 2020;Kewalramani et al, 2020;Stylianidou et al, 2018) and they have successfully proven that STEM module interventions can improve students' thinking skill and creativity. Similarly, several studies in Eastern countries (B Budi Setiawan et al, 2020;Kuo et al, 2019;Rasul et al, 2018;Shukri et al, 2019;Siew & Norjanah Ambo, 2018;Sirajudin et al, 2021) indicated that STEM approaches have a positive effect in developing and empowering creative thinking among elementary, secondary and universities students.…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to Katz (1999), dispositions are mental inclinations that make an individual respond in specific ways under specific conditions. Some of the typical examples of dispositions include creativity and curiosity (Bowman, Donovan, and Burns, 2001;Stylianidou et al, 2018). For one to develop scientific dispositions, one needs to receive experiences that stimulate and nurture specific mental habits required for scientific thinking (Beghetto and Plucker, 2006).…”
Section: Introductionmentioning
confidence: 99%